Improving patients' satisfaction in a mobile hospital using Lean Six Sigma – a design-thinking intervention. Issue 6 (25th April 2020) - Sunder M, Vijaya; Mahalingam, Sanjay; Krishna M, Sai Nikhil
Abstract: Lean Six Sigma (LSS) that offers a unique integration of Lean and Six Sigma has been accepted globally across services sectors. Previous studies that examined the application of LSS in healthcare were steered in traditional hospital settings. Apparently, there are no studies that highlight the application of LSS in mobile hospitals, an emerging trend in the healthcare sector. The aim of this article is to explore the applicability of LSS in a mobile hospital. The authors present a case study of improving patients' satisfaction in a mobile hospital, through reducing turnaround time. Design-thinking intervention to LSS helped resolve a real-time problem using Define-Measure-Analyze-Design-Verify roadmap. This article contributes to the 'healthcare quality" body of knowledge and is novel as it is the first of its kind of LSS application in a mobile hospital underpinning Design thinking. This study is unique as it demonstrates academia–industry collaboration in solving an organizational problem.